2023
DOI: 10.56553/popets-2023-0051
|View full text |Cite
|
Sign up to set email alerts
|

How Website Owners Face Privacy Issues: Thematic Analysis of Responses from a Covert Notification Study Reveals Diverse Circumstances and Challenges

Abstract: Many websites contain services from third parties. Misconfigurations of these services can lead to missing compliance with legal obligations and privacy risks for website users. Previous research indicates that one cause for such privacy issues is missing awareness. However, reasons for the missing awareness and other reasons for the prevalence of privacy issues are not widely researched; that includes website owners’ dealing with those issues. To shed light on the issue, we analyze 1043 responses from website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Research on websites' privacy notifications and cookie policies [26,48,79,96,97], as well as privacy information from apps [41,47,80] showed that software developers and companies were often unable to create notifications accurately. Further challenges were identified by analyzing general compliance to the legislation of apps [7,70] and monitoring conversations on privacy in online developer forums [63,84].…”
Section: Related Workmentioning
confidence: 99%
“…Research on websites' privacy notifications and cookie policies [26,48,79,96,97], as well as privacy information from apps [41,47,80] showed that software developers and companies were often unable to create notifications accurately. Further challenges were identified by analyzing general compliance to the legislation of apps [7,70] and monitoring conversations on privacy in online developer forums [63,84].…”
Section: Related Workmentioning
confidence: 99%